2002
DOI: 10.1034/j.1600-0692.2002.10562.x
|View full text |Cite
|
Sign up to set email alerts
|

Hot ductility of an Fe‐10%Ni alloy during penetration of copper

Abstract: Today's available theories for hot crack formation are based on the fact that hot cracks are formed in the presence of liquid films in the interdendritic areas or at the grain boundaries, which are exposed to tensile stress. Copper is well known to cause hot shortness in steels. In order to study how the liquid embrittles the material, high-temperature tensile tests were performed at two strain rates during the penetration of liquid copper into Fe-10%Ni. The penetration distance was measured in samples that we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This range is compared with the slightly higher ductility transition temperature range of 1673 K to 1723 K (1400°C to 1450°C) for an Fe-10Ni alloy containing only a negligible amount of Cu. [33] From thermodynamic calculations, the maximum solubility of Cu in austenite is predicted to be 13.9 wt pct with a nominal 6.5 wt pct Ni alloying addition (Figure 9). Beyond the point of maximum Cu solubility in austenite for the Fe-Cu-6.5Ni system, a sharp decrease in solubility is then observed up to the predicted liquidus temperature.…”
Section: F Discussion Of Hot Ductility Resultsmentioning
confidence: 99%
“…This range is compared with the slightly higher ductility transition temperature range of 1673 K to 1723 K (1400°C to 1450°C) for an Fe-10Ni alloy containing only a negligible amount of Cu. [33] From thermodynamic calculations, the maximum solubility of Cu in austenite is predicted to be 13.9 wt pct with a nominal 6.5 wt pct Ni alloying addition (Figure 9). Beyond the point of maximum Cu solubility in austenite for the Fe-Cu-6.5Ni system, a sharp decrease in solubility is then observed up to the predicted liquidus temperature.…”
Section: F Discussion Of Hot Ductility Resultsmentioning
confidence: 99%
“…However, A-286 has been found to be prone to intergranular fracture when it is deformed at high temperatures [4,5]. The issue of hot ductility loss has attracted much attention in the superalloy industry, and numerous studies have been reported [6][7][8][9][10][11]. Most of these studies have suggested impurities segregations and formation of precipitates along grain boundaries to be OPEN ACCESS responsible for loss of ductility.…”
Section: Introductionmentioning
confidence: 99%